Preliminary Investigation of a Novel 18F Radiopharmaceutical for Imaging CB2 Receptors in a SOD Mouse Model - Pascali, Giancarlo; Panetta, Daniele; De Simone, Mariarosaria; Burchielli, Silvia; Lucchesi, Valentina; Sanguinetti, Elena; Zanoni, Simone; Iozzo, Patricia; Saccomanni, Giuseppe; Manera, Clementina; Salvadori, Piero A. (Australian journal of chemistry, 2021)
We successfully radiolabelled a novel prospective cannabinoid type 2 receptor ligand with F-18 and tested its biodistribution in animal models by positron emission tomography (PET)/computed tomography (CT) imaging. The radiolabelling process was conducted on an alkyl mesylate fragment of the main naphthyridine core, using highly efficient microfluidic technology. No preliminary protection was needed, and the product was purified by semi-prep HPLC and SPE formulation, allowing the desired diastereomeric mixture to be obtained in 29% radiochemical yield and >95% radiochemically pure. SOD1(G93A) mice were used as model of overexpression of CB2 receptors; PET imaging revealed a significant increase of the tracer distribution volume in the brain of symptomatic subjects compared with the asymptomatic ones.